Multifocal epithelial hyperplasia: report of two cases - Radwan-Oczko, Małgorzata; Sender-Janeczek, Aleksandra; Kaczorowski, Maciej; Szczepaniak, Marta; Hałoń, Agnieszka (Journal of Stomatology, 2019)
Multifocal epithelial hyperplasia, also known as Heck’s disease, is not a common pathology, which is well-known to most physicians. Therefore, asymptomatic proliferation of the oral mucosa has been reported in the literature with differences in various geographic regions. Here, we report unique cases of multifocal epithelial hyperplasia involving multiple sites of oral cavity in a 59-year-old male and a 9-year-old boy.